Postoperative outcomes and functional results after Deloyer's procedure - a retrospective cohort study - Salgado-Nesme,Noel (2017)
ABSTRACT Introduction: The objective of our study was to describe surgical outcomes of Deloyers procedure in our referral center, and to compare the results of patients with and without protective ileostomy. Methods: Patients undergoing a Deloyers procedure from 2013 to 2016 were prospectively included. General characteristics, intraoperative variables, postoperative course, and functional outcomes were analyzed. Patients were compared into two groups: group (1) patients undergoing Deloyers procedure without ileostomy, and group (2) Deloyers procedure with protective ileostomy. Results: Sixteen patients undergoing isoperistaltic transposition of the right colon remnant were included, of which 9 (63%) were males with a median age of 47 (range 22-76) years. The main surgical indication was the restoration of bowel transit (62.5%). There was higher major morbidity rate in the Deloyers procedure with protective ileostomy group, but without statistical significance (20% vs. 9%, p = 0.92). No leaks or deaths were reported. The length of hospital stay was 7 days. The mean number of bowel movements per day was 4 at 18 months of follow up. Only four (25%) patients used irregularly loperamide. Conclusions: The Deloyers procedure has satisfactory results and is reproducible with low morbidity. The major and minor morbidity rates were similar between groups, suggesting that the costs and risks of a second procedure can be avoided by providing a safe primary anastomosis.